2011
DOI: 10.3758/s13421-011-0099-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on dual-task performance in children and adults

Abstract: Age effects on dual-task costs were examined in healthy adults (Exp. 1) and in typically developing children (Exp. 2). In both experiments, individual differences in performance on the single-task components were titrated so that any age differences in dual-task costs could not be attributed to differences in single-task performance. Dualtask costs were found, but there were no age-related differences in these costs in older relative to younger adults, in 7-year-old relative to 9-year-old children, or across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 63 publications
1
63
3
Order By: Relevance
“…Three studies reported improved DT performances from 4 years to 7–8 years (Dossett and Burns, 2000; Gautier and Droit‐Volet, 2002; McKenzie et al, 2003). However, the age differences were absent when the tasks were equated and performed under equal priority conditions (Anderson et al, 2011; Irwin‐Chase and Burns, 2000). The DTC were comparable between 7 and 9 year olds (Anderson et al, 2011); and between 10, 11 and 12 year olds (Imbo and Vandierendonck, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported improved DT performances from 4 years to 7–8 years (Dossett and Burns, 2000; Gautier and Droit‐Volet, 2002; McKenzie et al, 2003). However, the age differences were absent when the tasks were equated and performed under equal priority conditions (Anderson et al, 2011; Irwin‐Chase and Burns, 2000). The DTC were comparable between 7 and 9 year olds (Anderson et al, 2011); and between 10, 11 and 12 year olds (Imbo and Vandierendonck, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…However, the age differences were absent when the tasks were equated and performed under equal priority conditions (Anderson et al, 2011; Irwin‐Chase and Burns, 2000). The DTC were comparable between 7 and 9 year olds (Anderson et al, 2011); and between 10, 11 and 12 year olds (Imbo and Vandierendonck, 2007). The results for comparison of DT performances between children and adults were inconsistent (Anderson et al, 2011; Karatekin, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…However, we know that not all cognitive tasks interact with postural control processing in the same way. Previous studies have indicated that more difficult tasks may result in greater COP displacements due to attentional competition2, 3 ) . We hypothesized that a visual memory task would interfere with a balance task much more than a verbal memory task, because postural control is assumed to involve visual/spatial processing.…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence that temporary memory does not necessarily draw on processing capacity in working memory has come from a series of studies (e.g., Anderson, Bucks, Bayliss, & Della Sala, 2011; Baddeley, Logie, Bressi, Della Sala, & Spinnler, 1986; Baddeley, Bressi, Della Sala, Logie, & Spinnler, 1991; Cocchini, Logie, Della Sala, MacPherson, & Baddeley, 2002; Logie et al, 2004; MacPherson, Della Sala, Logie, & Wilcock, 2007; Salthouse, Fristoe, Lineweaver, & Coon, 1995) demonstrating that when healthy participants are asked to perform two distinct tasks concurrently (such as oral serial ordered recall of aurally presented digit sequences together with a perceptuomotor tracking task), then performance of each task is very little different from when performing only digit recall or performing only perceptuomotor tracking. This accumulated evidence suggests further that the processes thought to support oral serial recall, such as subvocal rehearsal, can operate even when a demanding gestural-motor task is being performed at the same time.…”
mentioning
confidence: 99%